The Missing Link in the Hart-Dworkin Debate. - Grabowski, Andrzej (Oxford Journal of Legal Studies)
Commentary by the translator on the publication of HLA Hart, 'The New Challenge to Legal Positivism (1979)' (2016) 36 Oxford Journal of Legal Studies 459.